Flatness and corrosion protection of polypyrrole film enhanced by two-dimensional g-C3N4 nanosheets. (December 2021) - Zhang, Meng; Zhang, Jie; Feng, Yu; Zhang, Xinyu; Guo, Ruijie; Yan, Hong
Abstract: In some researches, graphene was introduced into polypyrrole (PPy) film to enhance corrosion resistance. In this study, low-cost graphite-like (g-C3 N4 ) nanosheets were electrochemically co-deposited with PPy onto Q235 steel using dodecylbenzene sulfonic acid (DBSA) as a dopant. Due to the bridging of DBSA via hydrogen bonds, g-C3 N4 nanosheets were compatible with PPy film. The g-C3 N4 /PPy composite film was more compact and smoother than the PPy film, owing to the inhibition of g-C3 N4 sheets on the rapid growth of macromolecular structure. With the addition of g-C3 N4 sheets (11 wt%), the corrosion resistance of PPy film on the steel was further enhanced, with the corrosion current density decreased from 3.38 × 10 –5 to 2.54 × 10 –6 A·cm –2 .